2020
DOI: 10.1186/s13071-020-04436-0
|View full text |Cite
|
Sign up to set email alerts
|

Host-adaptation of the rare Enterocytozoon bieneusi genotype CHN4 in Myocastor coypus (Rodentia: Echimyidae) in China

Abstract: Background Enterocytozoon bieneusi is a zoonotic gastrointestinal pathogen and can infect both humans and animals. The coypu (Myocastor coypus) is a semi-aquatic rodent, in which few E. bieneusi infections have been reported and the distribution of genotypes and zoonotic potential remains unknown. Methods A total of 308 fresh fecal samples were collected from seven coypu farms in China to determine the infection rate and the distribution of genotypes of E. bieneusi from coypus using nested-PCR amplification o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Additionally, they have also been found in some animals from China. For instance, genotype KIN-1 has been found in pigs, cattle, deer, and goats (21)(22)(23)(24); genotype CHN4 in calf and coypus (25,26); and genotype Henan-III in NHPs, pet snakes, pigs, and birds (6,(27)(28)(29). The above results indicate that masked palm civets could harbor the different zoonotic genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, they have also been found in some animals from China. For instance, genotype KIN-1 has been found in pigs, cattle, deer, and goats (21)(22)(23)(24); genotype CHN4 in calf and coypus (25,26); and genotype Henan-III in NHPs, pet snakes, pigs, and birds (6,(27)(28)(29). The above results indicate that masked palm civets could harbor the different zoonotic genotypes.…”
Section: Discussionmentioning
confidence: 85%
“…Next to the reference number, in parentheses, is the geographic area/country of studied nutria population. a [17] (several sites/China); b [56] (several sites/China); c [11] (Atlantic Loire/France); d [15] (several sites/Czech Republic); e [11] (Atlantic Loire/France); f [15] (several sites/Czech Republic); g [51] (Norfolk, Suffolk/UK); h [57] (Texas/USA); i [58] (Curitiba/Brazil); j [12] (Malargüe/Argentine); k [13] (Buenos Aires, Argentina); l [18] (several sites/Czech Republic and Slovakia); m [52] (Lombardy/Italy); n this study (Lazio/Italy). The number after each taxon indicates author and year of description.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype XJP-II was previously found in pigs in Xinjiang ( Li D. F. et al., 2019b ), and NCF2 was also identified in farmed foxes ( Vulpes lagopus ) ( Zhang et al., 2016 ; Ma et al., 2020 ) and raccoon dogs ( Nyctereutes procyonoides ) ( Xu et al., 2016 ) in China, Kangaroo in Australia ( Zhang Y. et al., 2018 ). Genotypes EbpC, EbpA, and D were frequently found in humans and a broad range of animals ( Wang et al., 2013 ; Liu et al., 2017 ; Qi et al., 2018 ; Zhang X. X. et al., 2018 ; Zou et al., 2018 ; Wang H. et al., 2020 ; Wang Y. et al., 2020 ; Yu et al., 2020 ). The results showed that natural transmission of E. bieneusi among rodents, humans and many other animals may occur.…”
Section: Discussionmentioning
confidence: 99%